Changes in gene expression, cell physiology and toxicity of the harmful cyanobacterium Microcystis aeruginosa at elevated CO2 - Sandrini, Giovanni; Cunsolo, Serena; Schuurmans, J. Merijn; Matthijs, Hans C. P.; Huisman, Jef (Frontiers in Microbiology, 2015)
Rising CO2 concentrations may have large effects on aquatic microorganisms. In this study, we investigated how elevated pCO2 affects the harmful freshwater cyanobacterium Microcystis aeruginosa. This species is capable of producing dense blooms and hepatotoxins called microcystins. Strain PCC 7806 was cultured in chemostats that were shifted from low to high pCO2 conditions. This resulted in a transition from a C-limited to a light-limited steady state, with a ~2.7 fold increase of the cyanobacterial biomass and ~2.5 fold more microcystin per cell. Cells increased their chlorophyll a and phycocyanin content, and raised their PSI/PSII ratio at high pCO2. Surprisingly, cells had a lower dry weight and contained less carbohydrates, which might be an adaptation to improve the buoyancy of Microcystis when light becomes more limiting at high pCO2. Only 234 of the 4,691 genes responded to elevated pCO2. For instance, expression of the carboxysome, RuBisCO, photosystem and C metabolism genes did not change significantly, and only a few N assimilation genes were expressed differently. The lack of large-scale changes in the transcriptome could suit a buoyant species that lives in eutrophic lakes with strong CO2 fluctuations very well. However, we found major responses in inorganic carbon uptake. At low pCO2, cells were mainly dependent on bicarbonate uptake, whereas at high pCO2 gene expression of the bicarbonate uptake systems was down-regulated and cells shifted to CO2 and low-affinity bicarbonate uptake. These results show that the need for high-affinity bicarbonate uptake systems ceases at elevated CO2. Moreover, the combination of an increased cyanobacterial abundance, improved buoyancy, and higher toxin content per cell indicates that rising atmospheric CO2 levels may increase the problems associated with the harmful cyanobacterium Microcystis in eutrophic lakes.